Determinantes do desempenho escolar do município de Sobral - Alexandrino, Lariça Loiola Gonçalves (2017)
This dissertation intends to investigate the determinants of the school performance of the municipality of Sobral, through a panel data analysis including a threshold for Sobral, with data extracted from the School Census and the Brazil Test for the years 2007 to 2015. Thus, the main contribution of this study is that the results can elucidate on the influences for the educational success of the municipality of Sobral and that this be incorporated to fundamental public policies that aim to replicate such a model. It was observed that in a comparison between two schools with the same characteristics, the fact that one belongs to the Sobral network increases the expected average grade by more than 50%. In addition, among the covariates included in the model, the variable that showed the most consistency was "students per class", which had a negative effect that reduced the average grade of the two subjects between one and three percentage points more than the other schools northeastern The presence of laboratories, both computer science and science, was not relevant to a better grade in Portuguese, but the estimates infer that these can contribute to the increase of the Mathematics grade. The variable that represented the number of computers, showed a positive and significant correlation for the increase of the math grade, even though it was only 0.6%, but significant and the availability of internet access increased by approximately 2% the average of the two disciplines. The results point to variables not captured by the model, as the main determinants of the so-called Sobral Effect, among them, school management and pedagogical practices adopted.